The Economic Burden of Hospital Costs on Families With Type 1 Diabetes Mellitus Children: The Role of Medical Insurance in Shandong Province, China - Siyuan Wang; Yawei Guo; Elizabeth Maitland; Stephen Nicholas; Stephen Nicholas; Jingjie Sun; Anli Leng; Anli Leng (Frontiers Media S.A., 2022)
ObjectiveThis study estimates the economic burden imposed on families by comparing the hospitalization costs of T1DM children with and without medical insurance in Shandong province.MethodsOur data comprised 1,348 T1DM inpatient records of patients aged 18 years or younger from the hospitalization information system of 297 general hospitals in 6 urban districts of Shandong Province. Descriptive statistics are presented and regression analyses were conducted to explore the factors associated with hospitalization costs.ResultsChildren with medical insurance had on average total hospitalization expenditures of RMB5,833.48 (US$824.02) and a hospitalization stay of 7.49 days, compared with the children without medical insurance who had lower hospitalization expenditures of RMB4,021.45 (US$568.06) and an average stay of 6.05 days. Out-of-pocket expenses for insured children were RMB3,036.22 (US$428.89), which is significantly lower than that of the uninsured children (P < 0.01). Out-of-pocket (OOP) expenditures accounted for 6% of the annual household income of insured middle-income families, but rose to a significant 25% of the annual income for low-income families. These OOP expenditures imposed a heavy economic burden on families, with some families experiencing long-term financial distress. Both insured and uninsured families, especially low-income families, could be tipped into poverty by hospitalization costs.ConclusionHospitalization costs imposed a significant economic burden on families with children with T1DM, especially low-income insured and uninsured families. The significantly higher hospitalization expenses of insured T1DM children, such as longer hospitalization stays, more expensive treatments and more drugs, may reflect both excess treatment demands by parents and over-servicing by hospitals; lower OOP expenses for uninsured children may reflect uninsured children from low-income families forgoing appropriate medical treatment. Hospital insurance reform is recommended.